Maternal, paternal, and other caregivers' stimulation in low- and- middle-income countries. - Jorge Cuartas; Joshua Jeong; Catalina Rey-Guerra; Dana Charles McCoy; Hirokazu Yoshikawa (PLoS ONE, 2020)
Background and objectives Globally, studies have shown associations between maternal stimulation and early child development. Yet, little is known about the prevalence of paternal and other caregivers' stimulation practices, particularly in low- and- middle-income countries (LMICs). Methods Data from the Multiple Indicators Cluster Survey (MICS) and the Demographic and Health Survey (DHS) were combined across 62 LMICs (2010-2018). The sample included 205,150 mothers of children aged 3 and 4 years. High levels of stimulation were defined as caregiver engagement in at least 4 out of 6 possible activities with the child. The proportion of mothers, fathers, and other caregivers providing high levels of stimulation was calculated by country, region, and for the whole sample. Socioeconomic disparities within and between countries were estimated. Results On average, 39.8% (95% CI 37.4 to 42.2) of mothers, 11.9% (95% CI 10.1 to 13.8) of fathers, and 20.7% (95% CI 18.4 to 23.0) of other adult caregivers provided high levels of stimulation. Stimulation varied by region, country income group, and Human Development Index (HDI), with higher levels of maternal and paternal-but not other caregivers'-stimulation in high-income and high-HDI countries. Within countries, stimulation levels were, on average, lower in the poorest relative to the richest households, and some but not all countries exhibited differences by child sex (i.e., boys vs. girls) or area (i.e., urban vs. rural). Conclusions Results suggest a need for intervention efforts that focus on increasing caregiver stimulation in LMICs, particularly for fathers and in low-income contexts.